Pelatihan Pemanfaatan Google Classrom Sebagai Media E-Learning Sekolah - Tri Hastono; Ari Kusuma Wardana; Firdiyan Syah; Gunawan Gunawan; Ramdan Harjana (Pusat Riset dan Inovasi Nasional, 2021)
The use of information technology in the world of education looks better. With the ease of getting this information, cases of parents who do not know the status of their children's education are increasingly rare. The use of technology in the world of education in teaching and learning activities cannot be done by one party alone. It takes the involvement of all, especially teachers and students. If you look at the age of the teachers, of course, not a few of them can be considered old. This is what makes not a few of the teachers still rigid with technology. But it's a different story with today's school students. The year of birth of school students is currently in the generation Z category, where technology is their lifestyle. The method of transferring knowledge from teachers to students must be changed so that knowledge can be well absorbed by students. This community service aims to provide training on the use of Google Classroom as one of the school's e-learning at SMP N 2 Kasihan.